Relationship between automatic thoughts and mindfulness in patients with dual diagnosis: a correlational study - Kumar, Sunil; Malik, Deepak; Gupta, Arunima (International Journal Of Community Medicine And Public Health, 2023)
Background: Mental disorders are one of the leading causes of non-fatal disease burden and being experienced by population at large. To overcome the mental health issues like stress, depression, people experience of drug used. Using a substance and co-morbid with any type of illness exaggerate the overall health and using these known as dual diagnosis which pose a significant challenge for the professionals, stakeholders and family. The present study has been taken up to find out the relationship of automatic though and dispositional mindfulness amongst patients with dual diagnosis. Methods: A descriptive correlational study design was taken up for the present study, in which 150 male patients with dual diagnosis were selected and interviewed individually after ethical procedures, using Personal information schedule and Automatic thought questionnaire Scale, and Five Facet Mindfulness Questionnaire. Results: A total 150 patients were taken in this study. The majority (55%) were between the ages of 20 and 30, married (62%). Descriptive statistics and Pearson Correlation Coefficient were used to see the relationship among variables. The study showed a negative significant correlation of automatic thought and mindfulness at 0.01 level among patients with dual diagnosis. It also suggests a vicious cycle of negative thoughts and mindfulness in such patients. Conclusions: It was concluded that the automatic thoughts are negatively correlated with mindfulness. The current findings may help health professionals in providing better management to patients with dual diagnosis.